Selective estrogen receptor degraders with novel structural motifs induce regression in a tamoxifen-resistant breast cancer xenograft. Issue 3 (1st February 2019) - Govek, Steven P.; Bonnefous, Celine; Julien, Jackaline D.; Nagasawa, Johnny Y.; Kahraman, Mehmet; Lai, Andiliy G.; Douglas, Karensa L.; Aparicio, Anna M.; Darimont, Beatrice D.; Grillot, Katherine L.; Joseph, James D.; Kaufman, Joshua A.; et al.
Graphical abstract: Abstract: Potent estrogen receptor ligands typically contain a phenolic hydrogen-bond donor. The indazole of the selective estrogen receptor degrader (SERD) ARN-810 is believed to mimic this. Disclosed herein is the discovery of ARN-810 analogs which lack this hydrogen-bond donor. These SERDs induced tumor regression in a tamoxifen-resistant breast cancer xenograft, demonstrating that the indazole NH is not necessary for robust ER-modulation and anti-tumor activity.